PENGARUH PROMOSI JABATAN DAN KOMPENSASI TERHADAP MOTIVASI SERTA IMPLIKASINYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PERUSAHAAN MANUFAKTUR DI CIKARANG - ., Witarman (Jurnal Manajemen dan Bisnis Kreatif, 2017)
ABSTRACT This study aims to explain the influence of promotion and employee compensation to employee motivation that have implications on work productivity of manufacturing company in cikarang , in this study the sample used as many as 120 people with positions foreman and junior section head section production of manufacturing company in Cikarang. Data collection is done through direct observation, questionnaires, library research obtained through interviews and internal data collection of companies and relevant references. This research uses explanatory research type with quantitative approach. Method of data analysis using descriptive analysis method with path analysis. The result of the research shows that job promotion has a significant effect on work motivation 26,7%, compensation has significant effect to work motivation equal to 16,4%, and work motivation have significant effect to work productivity 22,8%, on the productivity of work has a significant effect of 8% smaller than the indirect effect of 54% through motivation, compensation does not directly affect the productivity of work and promotion positions, compensation and motivation simultaneously have a significant effect on work productivity of 61.9% while 38.1% is another influence that is not examined. Keywords: Motivation, Job Promotion, Compensation and Productivity